2005
DOI: 10.1016/s0753-3322(05)80010-1
|View full text |Cite
|
Sign up to set email alerts
|

Common carotid intima-media thickness is predictive of all-cause and cardiovascular mortality in elderly community-dwelling people: Longitudinal Investigation for the Longevity and Aging in Hokkaido County (LILAC) study

Abstract: Several cohort studies have examined the association of carotid intima-media thickness (IMT) with the risk of stroke or myocardial infarction in apparently healthy persons. We investigated the predictive value of IMT of cardiovascular mortality in elderly community-dwelling people, beyond the prediction provided by age and MMSE, assessed by means of a multivariate Cox model. Carotid IMT and plaque were evaluated bilaterally with ultrasonography in 298 people older than 75 years (120 men and 178 women, average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 8 publications
1
36
0
1
Order By: Relevance
“…For the analysis, we focused on the data given in 12 publications on these 8 studies, [2][3][4][5][6][7][8][9][10][11][12]19 which represent 37 197 subjects. Table 1 provides an overview of the studies in terms of the study design, definition of clinical end points, observed population, sample size, follow-up period, carotid segments studied, definition of IMT, model construction (which accounts for potential bias factors), and report of results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the analysis, we focused on the data given in 12 publications on these 8 studies, [2][3][4][5][6][7][8][9][10][11][12]19 which represent 37 197 subjects. Table 1 provides an overview of the studies in terms of the study design, definition of clinical end points, observed population, sample size, follow-up period, carotid segments studied, definition of IMT, model construction (which accounts for potential bias factors), and report of results.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, there are marked differences in age distribution, with a lower limit that ranges from 19 12 to 75 years. 19 Furthermore, the publications can be divided into 2 categories: those that use mean carotid IMT, determined from a number of IMT measurements at specific positions or by automated software over a segment of the artery, and those that use maximal carotid IMT. The Rotterdam Study is the only one in which IMT was determined by both methods in the same population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the relative predictive power of plaque or IMT measurements (either restricted to the common carotid or inclusive of bifurcation) is still debated. Most important, although several prospective intervention studies have shown that progression of IMT can be modified by antihypertensive and lipid-lowering agents, 8,16 -21 most of the prospective studies relating carotid IMT to cardiovascular outcomes have been observational, [1][2][3][4][5][6][7][9][10][11][12] and little is known of the relative predictive value of IMT measurements when modified by long-term treatment. Only data from a prospective observational study of plaque area progression 13 and from a very small interventional study, the Cholesterol Lowering Atherosclerosis Study 22 (CLAS), are available at present.…”
Section: Clinical Perspective On P 1090mentioning
confidence: 99%
“…A number of prospective population or cohort studies such as the Atherosclerosis Risk in Communities Study 1,2 (ARIC), the Rotterdam Study, 3,4 the Cardiovascular Health Study 5 (CHS), and the Carotid Atherosclerosis Progression Study 6 (CAPS), as well as several smaller studies, [7][8][9][10][11][12] have shown that carotid intima-media thickness (IMT) is significantly related to incident cardiovascular events, both coronary events and stroke. There is also evidence that plaque presence 4 and carotid plaque area 13 measured by ultrasound are predictive of subsequent cardiovascular events.…”
mentioning
confidence: 99%